The Impact of Auditor Time Budgeting Pressure on Fraud Detection Determinants - Linda Fransisca; Wahidahwati Wahidahwati; Titik Mildawati (Celebes Scholar pg, 2025)
This research examines the effect of professional skepticism, auditor competence, auditor experience, and time budget pressure on fraud detection ability and the impact of professional skepticism, auditor competence, and auditor experience on fraud detection ability with time budget pressure as a moderating variable. Furthermore, the research applies quantitatively with an explanatory approach. The data were primary, in the form of questionnaires. The variables were professional skepticism, auditor competence, auditor experience, time budget pressure, and fraud detection ability. Moreover, the respondents consist of auditors in KAP of East Java. The data analysis technique used moderated regression. As a result, it concludes that professional skepticism, auditor competence, auditor experience, and time budget pressure are proven partially on the fraud detection ability. Also, it moderates successfully the effect of professional skepticism, auditor competence, and auditor experience on fraud detection ability. Therefore, the results are used as an implication for auditors to increase professional skepticism, auditor competence, and auditor experience to improve fraud detection ability. In addition, KAP has to manage budget pressure well and control its policy which is not only oriented on time efficiency, but also audit quality.